The Design and Performance Analysis of DTMB System - Emy Haryatmi; Tubagus Maulana Kusuma; Busono Soerowirdjo; Purnawarman Musa (Universitas Ahmad Dahlan, 2016)
Various standard in digital television broadcasting system has been developed in the world, one of which is the Digital Terrestrial Multimedia Broadcasting, or abbreviated as DTMB that currently used by China and Hong Kong. DTMB has several standard configurations and parameters. In this research, DTMB system was designed and the results was validated through simulation using computer program, named Simulink. The parameters used in this research is the FEC with code rate of 0.4, 4QAM modulation, interleaver mode 1 and using a single carrier transmission mode. Stream format used in the simulation was MPEG2-TS as the input for DTMB system. Parameters selection was based on low implementation complexity, but with good results. Two important things in DTMB system is the existence of FEC and TDS-OFDM. FEC consists of cascaded BCH as the outer encoder/decoder (codec) and LDPC as the inner codec. The reason of using TDS-OFDM because it provides better picture quality when the receiver is in motion. The test results have shown that for static video, DTMB was able to receive video with identical quality compared to the original video, when the value of SNR=11dB and SNR=12dB for dynamic video. It is shown that after going through the process from LDPC to BCH, the number of bit errors decreased while the value of SNR increased.